Chemical Characterization and Antioxidant Activity of Apilarnil, Royal Jelly, and Propolis Collected in Banat Region, Romania - Dragoș Moraru; Ersilia Alexa; Ileana Cocan; Diana Obiștioiu; Isidora Radulov; Eliza Simiz; Adina Berbecea; Adrian Grozea; Monica Dragomirescu; Teodor Vintilă; Silvia Pătruică (Applied Sciences, 2024)
Bee products have a millennia-old tradition in human apitherapy, thanks to their numerous curative properties. The aim of this study was to perform a physicochemical characterization, including the percentage of water content, dry matter, pH, acidity, impurity content, protein, ash, and macro and micro minerals, and to evaluate the antioxidant activity of apiculture products, including apilarnil, royal jelly, and propolis. Samples were collected from our apiary in the Banat region of Romania in 2022 as well as from the market. Apilarnil and royal jelly were analyzed in pure and freeze-dried form, and propolis in pure and tincture form. Our results show that there is a large variability in the chemical composition and antioxidant activity of the three bee products studied, depending on the form of presentation and source of origin. In the case of commercial bee products, the best results were obtained in terms of chemical composition, including the content of macro and micro nutrients. All the samples analyzed showed acidity, pH, and impurity content values within the limits allowed by the quality standards. Apilarnil from our own apiary recorded the highest values for antioxidant activity, followed by propolis tincture and fresh propolis from own apiary.